Produção de lipases por leveduras isoladas do bagaço de caju utilizando fontes alternativas de Carbono e Nitrogênio - Freitas, Maria de Fátima Matos de (2017)
Lipolytic enzymes can catalyse a wide variety of reactions and are highly specific. For biotechnology, the need arises for the search for new microrganisms for this production. The objective of this work was to evaluate lipase production by two yeasts isolated from cashew bagasse, Candida tropicalis URM 7057 and Meyerozyma caribbica LABIOTEC 4 and to compare it with C. rugosa yeast NRRL Y-95. Synthetic culture media were initially tested for production of the enzyme. Synthetic medium C (containing glucose, KH2PO4, yeast extract, MgSO4 .7H2O, peptone and oleic acid) showed the best intracellular activity results (282 ± 14 in 48 h of cultive). Then, alternative medium culture was formulated with residues, in addition to ammonium sulfate and peptone, and evaluated the production of the enzymes of interest. Medium culture 01 contained molasses, medium culture 02, corn steep liquor (CSL), medium culture 03, olive mill wastewater (OMW) and medium culture 04, all of them. Medium 04 was better because it allowed the production of larger amounts of lipase, probably because it had a higher amount of nutrients for yeast. An experimental design was conducted to verify the influence of the concentrations of residues on lipase production. Corn steep liquor (CSL) had a positive effect on this production, providing extracellular lipase activity of 587 ± 5 U/L, in 24 h of cultive. The use of stirred tank bioreactors favored the production of lipases, since the activities of the lipase produced by C. rugosa in bioreactor were higher than those produced in flasks (600 U/L in bioreactor and 400 U/L in flasks, after 48 h of cultive) and for yeast C. tropicalis the enzymatic activity also presented in a larger quantity (close to 500 U/L, compared to 400 U/L in flasks). Biomass growth of yeast biomass C. tropicalis, in flasks and in bioreactor, was similar up to 48 h. The enzyme produced by C. rugosa has a molar mass close to 60 KDa, with an optimum pH of 7.0 and an optimum temperature of 40 °C. The partial biochemical characterization of the lipase produced by C. tropicalis showed that it presents an optimum temperature of 60 °C for the intracellular extract and 70 °C for the extracellular extract, optimum pH equal to 7.0. After adsorption of the enzyme in octyl-agarose, it was possible to identify, by zymogram analysis and by electrophoresis, bands close to those obtained for C. rugosa commercial lipase (60 KDa, 45 KDa and 22 KDa).